Utilization of Video Media Through the Discovery Learnig Model to Increase Learning Outcomes of Students with Respiratory System Materials in SMP N 1 Blangjerango Regency of Gayo Lues - Jumiati Jumiati; Hafnati Rahmatan; Safrida Safrida; khairil khairil; Abdullah Abdullah (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Keywords: Discovery Learning, Video Media, Learning Outcomes. Learners at SMP N 1 Blangjerango that so far in the process of teaching and learning biology, especially the respiration system material still uses conventional learning models, namely the learning process that rarely uses learning media to explain abstract respiration material so that it is difficult to understand and ultimately the learning outcomes do not reach KKM. The purpose of this study, to determine the use of video media through the Discovery Learning model on the respiration system material that can improve the learning outcomes of students of Blangjerango Junior High School 1. The approaches that can be used in this research are quantitative, experimental type and pretest-posttest control group design. The results of data analysis obtained the value of t_ (count) 2.78 and 〖t〗 table 1.72 it can be concluded that there is a significant difference in the results of learning achievement from the learning of the respiratory system in humans, so that the use of video media through the Discovery Learning model can improve student learning outcomes from the material system respiration at SMP N 1 Blangjerango, Gayo Lues Regency. Keywords: Discovery Learning, Video Media, Learning Outcomes. Learners at SMP N 1 Blangjerango that so far in the process of teaching and learning biology, especially the respiration system material still uses conventional learning models, namely the learning process that rarely uses learning media to explain abstract respiration material so that it is difficult to understand and ultimately the learning outcomes do not reach KKM. The purpose of this study, to determine the use of video media through the Discovery Learning model on the respiration system material that can improve the learning outcomes of students of Blangjerango Junior High School 1. The approaches that can be used in this research are quantitative, experimental type and pretest-posttest control group design. The results of data analysis obtained the value of t_ (count) 2.78 and 〖t〗 table 1.72 it can be concluded that there is a significant difference in the results of learning achievement from the learning of the respiratory system in humans, so that the use of video media through the Discovery Learning model can improve student learning outcomes from the respiration system material at SMP N 1 Blangjerango, Gayo Lues Regency.